Subjective Performance Evaluations and Reciprocity in Principal–Agent Relations1. (18th February 2014) - Sebald, Alexander; Walzl, Markus
Abstract We conduct a laboratory experiment with agents working on, and principals benefiting from, a real effort task in which the agents' performance can only be evaluated subjectively. Principals give subjective performance feedback to agents, and agents have an opportunity to sanction principals. In contrast to existing models of reciprocity, we find that agents tend to sanction whenever the feedback of principals is below their subjective self‐evaluations even if agents' pay‐offs are independent of it. In turn, principals provide more positive feedback (relative to their actual performance assessment of the agent) if this does not affect their pay‐off.